2020
DOI: 10.3390/genes11070778
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Complex Traits in Transgenic α-Synuclein Strains of Caenorhabditis elegans

Abstract: Different genetic backgrounds can modify the effect of mutated genes. Human α-synuclein (SNCA) gene encodes α-synuclein, and its oligomeric complexes accumulate with age and mediate the disruption of cellular homeostasis, resulting in the neuronal death that is characteristic of Parkinson’s Disease. Polymorphic variants modulate this complex pathologic mechanism. Previously, we constructed five transgenic introgression lines of a Caenorhabditis elegans model of α-synuclein using genetic backgrounds that are ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Indeed, it has become common practice for tracking single cells or even molecules in live C. elegans by using fully automated whole-animal imaging and quantitative analysis (33). Large C. elegans populations with target biomolecules marked by fluorescent probes can be subjected to highthroughput quantitative analysis with the Complex Object Parametric Analyzer and Sorter (COPAS) equipment (34)(35)(36)(37). These advances in quantitative C. elegans studies rely heavily on development of genetically encoded fluorescent probes or engineered chemical and nanoprobes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has become common practice for tracking single cells or even molecules in live C. elegans by using fully automated whole-animal imaging and quantitative analysis (33). Large C. elegans populations with target biomolecules marked by fluorescent probes can be subjected to highthroughput quantitative analysis with the Complex Object Parametric Analyzer and Sorter (COPAS) equipment (34)(35)(36)(37). These advances in quantitative C. elegans studies rely heavily on development of genetically encoded fluorescent probes or engineered chemical and nanoprobes.…”
mentioning
confidence: 99%
“…Taking advantage of their transparent body and small body sizes, C. elegans can be analyzed by flow cytometry and subjected to worm sorting using large-particle biosorter platforms(25). High-throughput quantitative single-cell analysis can therefore be performed on large C. elegans populations with target biomolecules marked by fluorescent probes(34)(35)(36)(37). In vivo fluorescent labeling techniques have shown great progress over the last decade and overcome limitations such as low sensitivity, low photostability, low brightness, high-background signal and incapacity to be utilized in vivo.…”
mentioning
confidence: 99%
“…In a previous study, we observed differences in protein expression of α-synuclein between strains NL5901 and SCH4856 while not for mRNA expression in C. elegans [161]. To visualize the α-syn::YFP expression in the N2 and CB4856 background, the YFP signal was observed in NL5901 and SCH4856 under a microscope, which represented the allocation of α-synuclein.…”
Section: Variance Of α-Synuclein Strains Nl5901 and Sch4856 On Mrna A...mentioning
confidence: 95%
“…Importantly, the replicability of pathological hallmarks in C. elegans provides a platform for studying disease [160]. For example, the expression of human α-synuclein in C. elegans caused inclusions containing α-synuclein aggregates, similar with the pathological phenotype of α-synuclein in human [43,161,162]. Together these traits made C. elegans to become a widely applied model organism for genetic variation PD research [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation